Pengaruh Minat Belajar dan Lingkungan Belajar Terhadap Hasil Belajar Pada Mata Pelajaran Ekonomi: The Influence of Learning Interest and Learning Environment on Learning Outcomes in Economics Subject - Azdkia, Fuji Nujul; Hermawan, H. Yoni; Nurdianti, Raden Roro Suci (COSMOS : Jurnal Ilmu Pendidikan, Ekonomi dan Teknologi, 2025)
This research was prompted by the low learning outcomes of students in the economics subject. The objective of this study is to analyze the influence of learning interest and the learning environment on student learning outcomes. The research method employed was a survey with an associative research design. The study population consisted of 179 eleventh-grade students of SMAN 1 Cihaurbeuti who were enrolled in Economics, with a sample of 124 students selected using a simple random sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression. The research findings indicate that learning interest and the learning environment each have a positive and significant effect on student learning outcomes, with a significance value of 0.000. Furthermore, both variables simultaneously have a significant influence on student learning outcomes. These findings suggest that an increase in learning interest and a conducive learning environment can contribute to the improvement of student learning outcomes in the Economics subject.